Stock and exchange rate movements in the MENA countries: A Markov Switching –VAR Model - Marwa Trabelsi; Slah Bahloul (Universitas Islam Indonesia, 2022)
Purpose ― This article explores the causal link between stock and currency returns in The Middle Eastern and North African (MENA) countries from January 2011 through February 2020. Methods ― This study uses the Vector autoregressive (VAR) and the Markov switching vector autoregressive (MS-VAR) models to investigate the dynamic causality between equity and exchange rate markets. Findings ― Results indicate that this relation depends on the state of the markets. Furthermore, generally, equity returns have a significant impact on the currency markets, whatever the market state. Implication ― Regime shifts in the relationship between stock and exchange rate markets are significant for portfolio allocation because they help investors improve their investment decisions through knowledge of the dynamic link between these markets. Originality ― This study adds to the literature on the relationship between exchange rates and stock prices in the MENA countries, which have become attractive destinations for international investors due to their higher returns.